A Review of Pathway Databases and Related Methods Analysis - Ghulam, Ali; Lei, Xiujuan; Guo, Min; Bian, Chen (Current Bioinformatics, 2020)
Pathway analysis integrates most of the computational tools for the investigation of high-level and complex human diseases. In the field of bioinformatics research, biological pathways analysis is an important part of systems biology. The molecular complexities of biological pathways are difficult to understand in human diseases, which can be explored through pathway analysis. In this review, we describe essential information related to pathway databases and their mechanisms, algorithms and methods. In the pathway database analysis, we present a brief introduction on how to gain knowledge from fundamental pathway data in regard to specific human pathways and how to use pathway databases and pathway analysis to predict diseases during an experiment. We also provide detailed information related to computational tools that are used in complex pathway data analysis, the roles of these tools in the bioinformatics field and how to store the pathway data. We illustrate various methodological difficulties that are faced during pathway analysis. The main ideas and techniques for the pathway-based examination approaches are presented. We provide the list of pathway databases and analytical tools. This review will serve as a helpful manual for pathway analysis databases.
Keywords: pathway algorithms